Socio-Cultural Factors Of Human Capital Development In Reducing Poverty - Sodirjonov Muhriddin Mahamadaminovich (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
This study examines the impact of socio-cultural factors on human capital development as a means to reduce poverty. Using a qualitative sociological approach, the research analyzes educational access, healthcare, and employment opportunities in Uzbekistan. Data were collected from policy documents, statistical reports, and interviews with social development experts. The results suggest that investments in education and social protection significantly enhance human capital, contributing to poverty reduction and sustainable economic growth.